Prevalence of Delivery Through C-Section Followed by the Induction of Labour in Nulliparous Patients Showing Undesirable Bishops Score - Kalsoom Habib Khattak, Sannia Furqan, Samina Bugti, Safiya Javed, Shazia Bibi, Saadia Shamsher (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inducing labour means induction of uterine contractions before natural labour, in order to deliver the fetus vaginally. It is done because birth through a C-section is riskier compared to vaginal delivery. For the purpose of induction and management of labour, Prostaglandins are used. Objective: The present study aims the determination the incidence of delivery by C-section in nulliparous pregnant women showing undesirable bishop’s scores. Study design: A cross-sectional study Place and Duration: This study was conducted at Timergarah Teaching Hospital Dir Lower Timergarah from January 2021 to January 2022 Methodology: A total of 150 nulliparous women were included in this study. The age of the patients ranged between 18 years to 35 years. All of the patients had singleton pregnancies having a cephalic presentation. The gestational ages of the patients ranged from 37 weeks to 42 weeks. All the patients had unfavourable bishop’s score which was equal to or less than 5. The patients showing reactive fetal heart rates were added to the study. None of the patients had any contraindications of vaginal delivery. Results: The present study included a total of 150 patients and 127 (84.67%) of them were in the age group between 18 years to 25 years. Overall68 (45.33%) of the patients were in the 40th week of pregnancy. The most common indication seen for the induction of labour was post-dated gestation in 70 (46.66%) patients. The incidence of C-section delivery was seen in 42 (28%) patients and the most common indication observed in these patients was the secondary arrest of labour. Keywords: Nulliparous, Dinoprostone gel, Induction of Labour, Bishop’s score